PERSEPSI GURU TERHADAP PENGGUNAAN MEDIA INTERAKTIF CANVA DALAM PEMBELAJARAN KOSAKATA BAHASA INDONESIA MURID KELAS III SDN 2 JAMBU HILIR BALUTI KABUPATEN HULU SUNGAI SELATAN - Fadhilah, Muhammad; Alimuddin A. Djawad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of digital learning media has become increasingly important in elementary education, particularly in creating learning activities that are attractive, interactive, and appropriate to students' characteristics. This study aimed to describe Teacher's Perception Towards the Use of Canva Interactive Media in Learning Indonesian Vocabulary of Grade III Students of SDN 2 Jambu Hilir Baluti, Hulu Sungai Selatan Regency. This research employed a qualitative approach with a case study design. The research subject was the third-grade teacher. Data were collected through interviews, limited participant observation, and documentation. Data analysis followed the Miles and Huberman (2014) interactive model, consisting of data reduction, data display, and conclusion drawing and verification. Data validity was examined through technical triangulation. The findings showed that the teacher had a positive perception of the ease of using Canva in preparing and implementing vocabulary learning. Canva was considered practical because of its templates and visual features that helped the teacher present learning materials attractively. The use of Canva was also perceived to increase students' interest, engagement, and understanding. Students appeared more enthusiastic, attentive, and actively involved in answering questions and participating in discussions. Visual elements such as images, colors, and designs helped students understand and remember vocabulary. However, several obstacles were identified, including the time required to prepare learning media, occasional internet connection problems, and the teacher's limited mastery of some advanced Canva features. Overall, interactive Canva media provided a positive contribution to Indonesian vocabulary learning in the third grade of elementary school.